Finance for housing an introduction - Davis, Cathy (Policy Press, 2013)
The global financial crisis of 2007-08 was triggered by sub-prime mortgage mis-selling in the US and the global sale of these debts as new bonds. Austerity programmes are designed to reduce the borrowing that governments undertook to stabilise failing banking systems but the UK's Coalition government is using 'austerity' as a cover to dismantle the welfare state. Housing is at the forefront of these changes. Mortgages and rental costs are rising as 'the market' dictates them, while people with low incomes now receive substantially less financial help from the welfare state. In this much-needed text by an experienced author with a policy background, current housing finance issues (and their history) are linked with broader social policy and political themes. It covers the finance of building and refurbishment, managing and maintaining property for all the different tenures (owner occupation, council housing, housing association and private renting), and discusses whether current arrangements are sustainable. Written for housing, social policy and politics students and staff, it is also accessible to anyone concerned about housing in Britain today.